Analysis of Learning Objectives Lesson Plan for Low Class Indonesian Thematic in the Implementation of the 2013 Curriculum - Anni Malihatul Hawa; Indah Rahmayanti; Lisa Virdinarti Putra; Ika Silfiana Arifatul Kh; Ela Suryani; Kartika Yuni Purwanti; Zulmi Roestika Rini (TALENTA Publisher, 2023)
This research is motivated by the obligation of a teacher in making a Lesson Plan (RPP in Indonesian language) prior to conducting instructional activities. Consequently, it is imperative for prospective teachers, specifically students enrolled in the PGSD programme at Ngudi Waluyo University, to possess the ability to effectively and accurately develop lesson plans in accordance with relevant regulations. The primary objective of this study is to examine the learning objectives of the theme RPP (Rencana Pelaksanaan Pembelajaran) in the Indonesian Language and Literature Learning course within the elementary school curriculum of 2013, specifically focusing on the low grade level. The participants in this study were randomly selected fourth-semester thematic RPP 3 students of PGSD at the University of Ngudi Waluyo. These students were enrolled in the Low Class Elementary School Indonesian Language and Literature Learning course. The employed methodology is the descriptive qualitative approach. Based on the findings derived from the analysis of the three thematic lesson plans, it can be deduced that there exists a congruence between the learning objectives outlined in the implementation of the 2013 curriculum and the objectives stipulated in the relevant laws and regulations. Each lesson plan demonstrates alignment with the analysed aspects, specifically: 1) the learning objectives under scrutiny, which encompass the intended learning outcomes as prescribed. The Core Competencies (KI) encompass various components, including spiritual attitudes, social attitudes, knowledge, and abilities. 2) The learning objectives are aligned with the Basic Competencies (KD). 3) The learning objectives incorporate Operational Verbs. 4) The learning objectives encompass the ABCD components.